Аутентичные тексты как инструмент обучения русскому языка в иноязычной аудитории; Казанская наука; № 3 - Волкова Т. Ф. Татьяна Фёдоровна; Воробьёва Л. В. Людмила Владимировна; Ильинская Т. Н. Татьяна Николаевна; Курикова Н. В. Наталья Владимировна; Тюрина И. И. Ирина Ивановна (2025, 2025)
Заглавие с экрана